2015
DOI: 10.1017/dmp.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the World Trade Center Disaster and 9/11-Related Post-Traumatic Stress Disorder and Household Disaster Preparedness

Abstract: Our findings indicate that prior 9/11 exposure favorably impacted Hurricane Sandy preparedness. Future preparedness messaging should target people with low social support networks. Communications should include information on evacuation zones and where to find information about how to evacuate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…While results are mixed, some studies on preparedness of disaster survivors have similarly shown that prior experience does not necessarily translate into current preparedness. In a recent study by Gargano et al, people who had been exposed to the World Trade Center (WTC) disaster had lower levels (18.8 %) of preparedness as compared to a national sample (25 %), although those with the greatest WTC exposure were most likely to have been prepared for Hurricane Sandy [43]. Motivation to prepare was also not influenced in our sample by the saliency of the disaster threat.…”
Section: Iscussioncontrasting
confidence: 52%
“…While results are mixed, some studies on preparedness of disaster survivors have similarly shown that prior experience does not necessarily translate into current preparedness. In a recent study by Gargano et al, people who had been exposed to the World Trade Center (WTC) disaster had lower levels (18.8 %) of preparedness as compared to a national sample (25 %), although those with the greatest WTC exposure were most likely to have been prepared for Hurricane Sandy [43]. Motivation to prepare was also not influenced in our sample by the saliency of the disaster threat.…”
Section: Iscussioncontrasting
confidence: 52%
“…A study of New York residents affected by Hurricane Sandy in 2012 found that those who had experienced previous trauma related to the attacks on the World Trade Centre were significantly more likely to evacuate and become displaced. 30 As noted above, our control for confounding by reported pre-existing illness would have controlled for this to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents who lost power during Superstorm Sandy were not more likely to perceive their households as prepared or actually be prepared. Findings on the relationship between prior disaster experience and preparedness have been mixed [ 47 – 49 ]. A wide variety of factors likely influence this relationship, including the frequency and severity of outages experienced.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be misclassification of prior outage experience because we only asked about Sandy. Respondents may have had a range of previous power outage experience, in addition to other disaster experiences, such as the September 2001 World Trade Center terrorism attack, which could have influenced preparedness [ 47 ].…”
Section: Discussionmentioning
confidence: 99%